Avaliação da carbonização e sulfonação simultâneas de material celulósico e lignocelulósico para obtenção de catalisador ácido sólido e carbon dots - Souza, Mateus Cristian Gomes (2022)
The development of solid acid catalysts (SACs) in order to replace concentrated acid solutions, used in many industrial processes, has drawn great attention in recent years for presenting several advantages, mainly the possibility of recovery and reuse of heterogeneous catalysts. Carbon-based SACs stand out for the possibility of being produced by relatively simple and inexpensive paths, using accessible and renewable sources, usually produced by the sulfonation of previously carbonized materials. In the present work, the production of SACs was evaluated through the simultaneous carbonization and sulfonation of microcrystalline cellulose (MCC) and a biomass residue (Moringa oleifera pods, VM) by the direct reaction of these materials with concentrated sulfuric acid (H2SO4). The possibility of producing carbon dots (CD) was also evaluated once the emission of fluorescence from the supernatant was detected. The physical-chemical and structural characterizations showed no differences between the catalysts obtained from the two raw materials, although the MCC products showed better reuse results. Among the conditions studied, the SACs were successfully produced with temperature of 125 °C and reaction time of at least 60 minutes, yielding up to 62 % by mass and a total acid sites concentration reaching 1.3 mmol g-1, relatable with the ones presented by other works in the literature. X-Ray Diffraction (XRD) and Raman Spectroscopy analyzes indicate a structure consisting of randomly organized graphitized fragments; while Attenuated Total Reflectance Infrared Spectroscopy (ATR-FTIR) spectra indicates the presence of sulfonic groups (-SO3H) attached to the carbonic material. In oleic acid esterification experiments, yields of up to 89% were obtained with 6 h of reaction, using 5% of catalyst and methanol in a molar ratio of 1:20, which indicates a good catalytic capacity of the materials that, despite decreasing within cycles of reuse, it can be regenerated by treatment of spent catalyst with H2SO4. Analyzes of the supernatant separated during the preparation of the SACs indicated the production of CDs simultaneously with the carbonization/sulfonation process; therefore, the production of CDs from carbonized materials was tested by treating these materials with nitric acid (HNO3) and ultrasound. Fluorimetry studies indicates that the fluorescence of the obtained CDs is influenced by the pH of the medium and its emission is dependent of the excitation wavelength, making them potentially applicable as photocatalysts. In this way, the processes presented in this work allows to obtain SAC and CDs that can act as catalysts in a series of physical-chemical processes.